Monsoon variability and high latitude climate signals in the central Mediterranean at the Pliocene – Pleistocene transition: the Gelasian stratotype section (Monte San Nicola, Sicily) - Addante, Marina; Herbert, Timothy D.; Girone, Angela; Caruso, Antonio; Marino, Maria; Scopelliti, Giovanna; Fasone, Stefano; Maiorano, Patrizia (Global and Planetary Change, 2025)
An integrated high-resolution climate framework is reconstructed at the Monte San Nicola GSSP section (Southern Sicily), the type-section for the Lower Pleistocene Gelasian Stage. Our multiproxy record is based on planktonic foraminiferal stable oxygen isotopes, alkenones and calcareous plankton assemblages, focusing on the interval between ∼2.7 and 2.5 Ma, which includes the Gelasian GSSP. Calcium carbonate content and sediment colour analyses are used to integrate lithological field observations. We provide the first high-resolution Mediterranean Sea Surface Temperature (°C) record, between MIS G4 and the onset of MIS 99 in the Monte San Nicola type-section and extend the calcareous plankton and oxygen isotope dataset published in a previous paper. The results enable to: i) highlight modifications in surface water dynamics related to African monsoon activity and North Atlantic climate variability; ii) strengthen the evidence that the first significant southward migration of the Subarctic Front in the mid-latitudes occurred during MIS 104, slightly below the GSSP, concomitant with strengthening of the winter monsoon over the Chinese loess plateau; iii) reveal the occurrence of millennial-scale variability during glacials, correlated to North Atlantic Ice Rafted Debris events within MIS 104 and MIS 100. The results provide evidence that the paleoclimate and stratigraphic signals are very well preserved in the type-section and further improve the correlation potential of the GSSP outside the type-area.